(untitled) - Cerra, Allison (Hoboken, N.J., 2013)
This book: Addresses how new technology trends - including mobility, cloud, big data and collaboration - are fundamentally changing the way work is conducted and how company leadership can tap into these trends to affect positive cultural reform ; Examines how the introduction of new technologies and the emergence of new business models are shifting traditional organizational roles, including HR, marketing, finance, and IT ; Takes an in-depth look at how the next-generation of top talent, represented by college students at the top universities, view their future workplace environment and how technology can become a meaningful magnet for recruitment and retention ; Zeroes in on how the integration of technology into the workplace differs between the United States and China and the implications to the global marketplace. What emerges from this book is an evolved role for company leadership, one of significant strategic value as cultural stewards capable of generating sustainable advantage for their companies in the most competitive market witnessed in decades.
Keywords: Information technology,Công nghệ thông tin; Management,Quản lý